2015
DOI: 10.1167/iovs.14-16344
|View full text |Cite
|
Sign up to set email alerts
|

Visual Prognosis of Eyes Recovering From Macular Hole Surgery Through Automated Quantitative Analysis of Spectral-Domain Optical Coherence Tomography (SD-OCT) Scans

Abstract: A lowering extent of EZ band defects in the foveal and parafoveal regions is a good indicator of postsurgery VA recovery. Attention should also be given to postsurgical alterations in the inner retina, as patients with more extensive atrophic changes appear to have slower or worse VA recovery despite closure of the macular hole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…A reliable automated segmentation approach, such as that presented herein, is crucial to enabling such work. Our work has also shown superior results to other state-of-the-art clinical software in eyes affected by hydroxychloroquine toxicity [15] and post-surgical macular hole eyes [6]. We plan to expand our segmentation method to SD-OCT scans acquired in the region surrounding the optic disc as well as to eyes presenting with other retinal pathologies, such as glaucoma and retinitis pigmentosa.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A reliable automated segmentation approach, such as that presented herein, is crucial to enabling such work. Our work has also shown superior results to other state-of-the-art clinical software in eyes affected by hydroxychloroquine toxicity [15] and post-surgical macular hole eyes [6]. We plan to expand our segmentation method to SD-OCT scans acquired in the region surrounding the optic disc as well as to eyes presenting with other retinal pathologies, such as glaucoma and retinitis pigmentosa.…”
Section: Discussionmentioning
confidence: 90%
“…Our method is sought to address the aforementioned challenges of prior algorithms, producing accurate delineations of the intraretinal layered structure in scans acquired during clinical practice and maintaining a stable behavior in disease cases while also producing accurate outlines that follow the particular pathologies of the disease, not smoothing out important details. This method was used previously for the segmentation of the retina in hydroxychloroquine toxicity [15] and postsurgery in macular hole cases [6]. In these applications, the results of our methods were successful and superior to current commercial software by visual inspection, but details about the method and its evaluation have not yet been published.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A study by de Sisternes et al [30] revealed that eyes that recently underwent MH repair surgery not only exhibited defects in the ellipsoid zone band, but also showed obvious damage in the inner retina layers when compared to the nonsurgical fellow eyes. Studies also demonstrated that the structure of the inner retina did not recover rapidly after MH surgical repair, in contrast to the ellipsoid zone band region, which quickly recovered [30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies also demonstrated that the structure of the inner retina did not recover rapidly after MH surgical repair, in contrast to the ellipsoid zone band region, which quickly recovered [30][31][32][33] . Surgical damage of the inner retinal layers may also affect the retinal capillary plexus, and a reduced flow index in the capillary plexus may impede the healing of inner retinal layers.…”
Section: Discussionmentioning
confidence: 99%